2007
DOI: 10.1038/sj.jcbfm.9600502
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of the 70 kDa Heat Shock Protein in Experimental Stroke

Abstract: The 70-kDa heat shock protein (Hsp70) is involved in protecting the brain from a variety of insults including stroke. Although the mechanism has been largely considered to be because of its chaperone functions, recent work indicates that Hsp70 also modulates inflammatory responses. To explore how and whether Hsp70 regulate immune responses in brain ischemia, mice overexpressing Hsp70 (Hsp Tg) were subjected to 2 h middle cerebral artery occlusion, followed by 24 h reperfusion. Parallel experiments were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
186
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(199 citation statements)
references
References 43 publications
8
186
1
Order By: Relevance
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 88%
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 88%
“…192 Using cocultures of astrocytes and microglia, HSP-70 transgenic microglia cultured with wild-type astrocytes experienced less injury to oxygen glucose deprivation (OGD) than did wild-type microglia cultured with wild-type astrocytes. 193 In a transgenic mouse model of HSP-70 overexpression, protection from experimental stroke was associated with decreased microglial activation. 193 Protein binding studies suggest that this is due to HSP-70 binding to the NF-B complex and blocking I B phosphorylation.…”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%
“…193 In a transgenic mouse model of HSP-70 overexpression, protection from experimental stroke was associated with decreased microglial activation. 193 Protein binding studies suggest that this is due to HSP-70 binding to the NF-B complex and blocking I B phosphorylation. 193 This anti-inflammatory may be due to the ability of HSP-70 to inhibit NF-B activation.…”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%
See 2 more Smart Citations